The Influence of Lean Management Practices on Port Logistics Performance in Tanzania: A Case of Dar es Salaam Port - Mwambipile, Joseph; Ryoba, Chacha (AGUSPATI Research Institute, 2025)
This study examined the influence of lean management practices on port logistics performance in Tanzania, focusing on waste elimination, continuous improvement, and cycle time reduction. Guided by the Resource-Based View theory, which emphasizes internal resources and capabilities as drivers of efficiency, the research aimed to determine how lean practices enhance operational effectiveness and create value for port stakeholders. A quantitative research design was employed, targeting 1,454 port personnel. Stratified random sampling was used to select 314 respondents, including clearing and forwarding agents, shipping agents, and transporters, as these groups directly shape logistics efficiency at Dar es Salaam Port. Data were collected through structured questionnaires and analysed using descriptive statistics, correlation, and multiple regression. The findings revealed that cycle time reduction had the most significant effect on logistics performance, highlighting that optimizing cargo handling, vessel discharge, and clearance processes strongly improves efficiency. Waste elimination also showed a positive and significant effect, indicating that minimizing redundant processes and inefficiencies contributes meaningfully to operational gains. Similarly, continuous improvement practices such as employee engagement, process refinement, and feedback-driven initiatives were found to significantly enhance logistics performance. The study extends the Resource-Based View theory by demonstrating the relevance of lean practices in a developing country’s port logistics context, emphasizing the importance of internal capabilities and process optimization. Practically, the research provides insights for port authorities and policymakers to adopt integrated lean strategies, strengthen digitalization, and promote employee involvement to improve efficiency. Future studies are recommended to examine additional lean dimensions and undertake comparative analyses across ports to improve generalizability.